Changes in selected vitamins, microorganism counts, and sensory quality during storage of pressurised sprouted seed of alfalfa (Medicago sativa L.) - Dana Gabrovská; Ivana Paulíčková; Eva Mašková; Vlasta Fiedlerová; Kateřina Kocurová; Jiřina Průchová; Jan Strohalm; Milan Houška (Czech Journal of Food Sciences, 2005)
The aim of this study was to examine the changes of nutritional and sensory quality of sprouted alfalfa seed treated by high pressure, that take place during storage. Along with this, microbiological safety was also observed. Sprouted alfalfa seed in citric acid pickle, packed in transparent laminated bags PA/PE 80, was treated with 500 MPa high pressure for 10 minutes. The processed seed in bags was stored in a refrigerator for 21 days. The bags were sampled in regular intervals to perform analyses. The changes in the contents of vitamin C, riboflavin, niacin, and pantothenic acid were observed during storage. The same samples were also checked for microbiological safety and sensory quality. Vitamin C showed a significant decrease during storage. The content of vitamin C fell markedly after high pressure treatment (by 77%) and further decreased by 10-20% during storage. The values of riboflavin content did not change very much as a consequence of pressurisation or the storage period. The contents of niacin and pantothenic acid kept decreasing until the 3rd day of storage by some 60% in total and then remained unchanged. Sensory descriptors indicated quality decrease. High pressure treatment damaged the tissues of sprouted alfalfa seed which subsequently manifested itself particularly in the deterioration of appearance and texture quality. An additional overall impairment of the seed appearance and texture occurred during its storage. Microbiological safety of sprouted alfalfa seed was preserved throughout the storage time.